The evolution of social wasps - Hunt, James H. (Oxford : Oxford University Press, 2007)
'The Evolution of Social Wasps' resolves one of evolution's most intriguing problems - the origin of insect sociality. It also challenges conceptual approaches that have dominated three decades of social behaviour research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Vespidae -- Behavior; Social behavior in animals